Perspectives in the design and application of composites based on graphene derivatives and bio‐based polymers. Issue 12 (11th August 2020) - Chen, Siyu; Yang, Kou; Leng, Xuanye; Chen, Musen; Novoselov, Kostya S; Andreeva, Daria V
Abstract: Two‐dimensional materials (2DMs), especially graphene derivatives, have attracted a wide range of interest in science and technology because of their exceptional physical and chemical properties and large potential application areas in electrochemistry, photonics, bioengineering, electronics and membrane separation fields. Our review focuses on recent advances in the construction of new functional composites using graphene oxide (GO), reduced graphene oxide (rGO) and bio‐based macromolecules. The incorporation of bio‐based polymers into GO and rGO nanolayers provides a novel way to tailor the properties of 2DMs. Meanwhile, 2DMs/bio‐based polymer composites are sustainable and biocompatible. Benefiting from the combination of superior properties of both materials, they are endowed with new functions and new application areas. Here, we compare existing fabrication approaches for 2DMs/bio‐based polymer composites. Then, we highlight the properties of composites such as ionic conductivity, molecular transport, mechanical properties, biocompatibility and sustainability. Finally, we discuss recent progress in applications of 2DMs/bio‐based polymer composites for efficient ionic and molecular separation technologies, the construction of energy‐related devices including fuel cells and transistors, and biomedical engineering. © 2020 Society of Industrial Chemistry Abstract : Graphene derivatives/bio‐based polymer composites possess preeminent properties and have become highly promising candidates for various cutting‐edge applications, such as efficient membrane separation technologies and the construction of energy‐related and bionic devices.